TEACHING SOCIAL SKILL THROUGH MULTICULTURAL EDUCATION AS AN ALTERNATIVE TO IMPARTING DIVERSITY - - Sariyatun (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Education in multicultural society and global society environment should equip the students tohave cognitive ability and interpersonal skill in order to learn and to work, and to live withothers, coming from different race, religion, language and cultural background. For thatreasons, education should be prepared to have attitude to be ready to cooperate and skill tocreate cooperation. Without social skill, human beings cannot interact with otherscorresponding to the role in social structure existing in their environment. The best means ofbuilding and socializing multicultural concept in order to bring about conducive social behaviorconstituting “Social wisdom”, “cultural wisdom”, and “moral wisdom”, and noble character is“multiculturalism education”.Keywords: Social Skill, Multicultural education.